Answers

2014-11-14T10:57:25+08:00
E.g. 2x-3y=-2
       4x+y=24
solution: solve the equation which is more simple and easy.
        y=-4x+24
Substitute the value of Y to the first equation
        2x-3(-4x+24)=-2
Then solve for the vaue of X
         2x+12x-72=-2
         14x=72-2
          14x=70
         14x/14=70/14
 X=5
 Substitute the value of x to the second equation or to the value of Y
           4x+y=24
           4(5)+y=24
           20+y=24
           y=24-20
Y= 4
or:
           y=-4x+24
           y=-4(5)+24
           y=-20+24
Y=4
The answer/ solution now is:
(5,4)

0